PENGARUH PENERAPAN METODE INKUIRI TERHADAP KEMAMPUAN MATEMATIKA SISWA KELAS VIII SMP NEGERI 1 PADANG-GANTING KABUPATEN TANAH DATAR (Jurnal Pelangi : Research of Education and Development, 2011)
The cause of the low understanding concepts and students' problem-solvingabilities in mathematics at SMP Negeri 1 Padang-ganting Tanah Datar is because themethods of teaching that is still centered on the teacher. The students were not involvedactively in teaching and learning process. One of the efforts done to overcome the aboveproblem is to use the inquiry method. The purpose of this researc is to determine: (1) Isthe high group problem-solving ability in the experimental class better than the highgroup problem solving in the control class. (2) Is the low group problem-solving abilityin the experimental class better than the low group problem solving in the control class.(3) Is the ability of understanding concept of the high group in the experiment class betterthan the understanding concept of high-class control group. (4) Is the ability of poorunderstanding concept on the experimental class better than the understanding concept oflow group on the control class.This research was conducted at the eighth grade students of SMP Negeri 1Padang-ganting school year 2010/2011. The method was Quasi Experiment with thedesign of the Control Group posttest design. The experiment group was treated with theinquiry method of learning and the control group with normal learning. Data werecollected through the mathematic achievement test.The results showed that: (1) high group problem-solving skills in the experimentclass was better than the high group problem solving in the control class,(2) the low group problem-solving ability in the experiment class was better than the lowgroup problem solving in the control class, (3) the ability of understanding concept of thehigh group in the experiment class was better than the understanding concept of highclasscontrol group. (4) the ability of poor understanding concept on the experiment classwas better than the understanding concept of low group on the control class.